Cultivo do melão “gália” em diferentes concentrações de nitrogênio e potássio na fertirrigação - Silva, Karen Mariany Pereira (2018)
The objective of this work was to evaluate the response of the "Gaul" melon submitted to nitrogen and potassium concentrations in fertirrigation, in two types of soils, being a characteristic Argisol and Cambisol in the melon producing region of Mossoró / RN. The experiments were carried out in a greenhouse belonging to the Universidade Federal Rural do Semi-Árido - UFERSA. The experimental design was a randomized block design consisting of thirteen treatments, with four replications. The plants were conducted under controlled fertirrigation by varying nitrogen and potassium concentrations. The treatments were based on the concentration considered standard for the hydroponic cultivation of melon (168 and 234 mg L-1 of N and K), and from these were adopted 5 levels of factors N and K (0, 50, 100, 150 and 200%), for each soil, that, combined by the double square experimental matrix, allowed to form 13 treatments. The characteristics evaluated in the culture were: vegetative and nutritional development of the plants, production and fruit quality, besides changes in soil fertility. The data were submitted to analysis of variance and regression analysis for response surface. The concentrations of nitrogen and potassium, caused effects on the growth, production and quality of the fruits. For the Argisol, it was observed that the increase of N concentrations provided higher yield and fruit quality. For Cambisol, the best yield was for intermediate doses of nitrogen and there was negative response to potassium